(untitled) (Research, Society and Development, 2025)
The present study aimed to analyze the biosafety measures implemented in autopsy laboratories, with emphasis on identifying the main occupational risks and evaluating the preventive strategies adopted to reduce professionals’ exposure to infectious agents and potentially hazardous biological materials. An integrative literature review was conducted with a search in the Medline/PubMed database. Eight articles that directly addressed biosafety measures in autopsies were selected. The analysis revealed a diversity of risks, highlighting the generation of aerosols, sharps accidents, and exposure to chemical agents and pathogens, including SARS-CoV-2. The analysis of the studies evidenced that biological risks, particularly the inhalation of aerosols generated by oscillating saws and liquid aspiration, are predominant. Inadequate infrastructure, such as the lack of negative pressure rooms (Biosafety Level 3 - BSL-3), and failures in the use of Personal Protective Equipment (PPE) and waste management amplify these dangers. Effective strategies include proper facility design, the adoption of additional physical barriers (such as the “craniotomy box”), controlled ventilation, and permanent staff education. It is concluded that the rigorous adoption of biosafety measures, aligned with international guidelines and supported by adequate infrastructure and continuous training, is imperative to mitigate occupational risks in autopsy laboratories. Such actions are essential to ensure professional safety, the quality of forensic procedures, and the protection of public health.